El progresismo político como estrategia regional en América del Sur para la promoción del desarrollo humano - Mendieta Navarrete, Erick Fernando (My University, 2021)
This essay is based on the research guidelines of the technical university of Machala and responds to the approach of the following problem which is: is there a condition of correspondence between the pragmatic actions of the regimes inserted in political progressivism and the achievements of development human in Latin America? Given that the general objective corresponds to having the purpose of giving a solution or answer to the problem described above, an investigation was carried out with a totally qualitative methodology, where the epistemological approach used is the rational-deductive one. The research work is directed through the sociological current of critical theory, which provides a variety of theories that are contrary to capitalist ideology, in this sense it gives greater contribution to the positioning of progressive governments that excelled in the region from South America. The 21st century has been characterized by the arrival and conquest of progressive governments or also recognized as "leftists" in political and social power, since their ideology faced the right, the latter was the cause of the foreign debt that many countries of the Latin American region were emerged and could not stand out.
El presente ensayo se fundamenta en los lineamientos de investigación de la universidad técnica de Machala y responde al planteamiento de la siguiente problemática que es: ¿existe una condición de correspondencia entre el accionar pragmático de los regímenes insertos en el progresismo político y los logros de desarrollo humano en América Latina? Dado que el objetivo general corresponde en tener como finalidad dar una solución o respuesta al problema descrito anteriormente, se realizó una investigación con metodología totalmente cualitativa, donde el enfoque epistemológico utilizado es el racional- deductivo. El trabajo de investigación se encamina a través de la corriente sociológica de la teoría critica, misma que aporta una variedad de teorías que son contrarias a la ideología capitalista, en este sentido le da mayor aporte al posicionamiento de los gobiernos progresistas que sobresalieron en la región de América del Sur. El siglo XXI se ha caracterizado por la llegada y conquista de los gobiernos progresistas o reconocidos también como “izquierdistas” en el poder político y social, ya que su ideología enfrentaba la derecha, esta última era la causa de la deuda externa que muchos países de la región de Latino América estaban emergidos y no podían sobresalir.
Keywords: GOBIERNO PROGRESISTA; MOVIMIENTO SOCIAL; DESARROLLO HUMANO; POLITICA SOCIAL